(ANALYSIS OF THE EFFECT OF WORK STRESS AND MOTIVATION ON EMPLOYEE PERFORMANCE AND JOB SATISFACTION AS AN INTERVENING VARIABLE IN PT PERTAMINA (PERSERO) MOR I MEDAN) - Ummi Fauziyah; Nazaruddin; Zahari Zen (CV. Radja Publika, 2026)
Based under law no. 22/2001, Pertamina's monopoly business rights revoked, in other words the Pertamina had the same position with another company. It has certainly spurred the entire marketing units of Pertamina such as Marketing Operation Region (MOR) I to improve the quality of companies, one of them by improving the performance of employees. Many factors can influence the performance of the employee, but in this study used a variable work stress and motivation to analyze the influence of the performance of employees with job satisfaction as an intervening variable. As for the purpose of this research was to analyze the effect of work stress and motivation on performance of employees both directly and through job satisfaction as well as to formulate a policy to improve the performance of the employees of PT Pertamina (Persero) MOR I. This research used a survey approach by spreading the questionnaire directly to the 105 respondents. Furthermore, the data were analyzed by using statistical modeling techniques of SEM (Structural Equation Modeling) using AMOS 22. Based on the results obtained work stress had a negative effect on the performance of employees both directly and through the variable job satisfaction, while the influence of motivation was positive on the performance of employees both directly and through job satisfaction. In other words, the motivation is the most influential factor in improving employee performance, while the work stress is a factor that can degrade the performance of the employee. Therefore, it is necessary to make real efforts to improve employees' performance by evaluating and improving the system of career development and assessment of work achievement, improving relations between superiors and subordinates, doing a relaxation, providing a container to accommodate ideas either advice or criticism, as well as creating a work environment that is safe and comfortable. With performed all of activities are expected performance will be increased.